Understanding geographical inequalities through the construction of a Risk of NEET Index for local authorities. - Addario, Gianfranco; Wilson, Charles (International Journal of Population Data Science, 2025)
The ONS estimates that 13.4% of young adults in the UK were not in employment, education or training (NEET) in the last quarter of 2024. The effect of having experiences of NEET is scarring for young adults, as NEET is associated to poorer financial and wellbeing outcomes later in life. The national economy is affected too, with public finances being negatively impacted by the proportion of young adults who are NEET. How can we understand who is at risk of NEET? How can we help them move towards economic activity? This information is crucial for schools and local authorities, who have the power to help pupils facing the greater risk. In 2023, we produced an index to measure the risk for a young adult to experience NEET using survey data. While this provided insights at a national level, it could not be used to understand the geographical dimensions of NEET. In this project, supported by the Youth Futures Foundation and the Blackpool Council, we sought to reproduce the Risk of NEET index (RONI) using data available in school and local authorities, with the aim of facilitating the understanding and the monitoring of NEET risk in a local setting. This analysis used the LEO dataset. Risk factors to NEET were sourced from educational data, and their importance was calibrated on different post-16 outcomes observed in employment, benefit, and further education data. Risk factors were identified in focus groups with individuals battling NEET in their day-to-day jobs in schools, colleges and local councils. This project contributed to understand geographical variations of NEET and risk factors in England. While the analysis is not completed yet, our initial findings suggest that local authorities differ both in how common risk factors are and in their effect on being NEET. The evidence indicates that geographical inequalities do not manifest only through a greater prevalence of disadvantage, but also through the severity of the different pathways leading to negative outcomes.